2004
DOI: 10.1111/j.1464-5491.2004.01374.x
|View full text |Cite
|
Sign up to set email alerts
|

Near patient blood ketone measurements and their utility in predicting diabetic ketoacidosis

Abstract: Measuring beta-OHB when a hyperglycaemic patient is identified could offer a simple method of identifying at an early stage those patients at highest risk of DKA (beta-OHB > 3.0 mmol/l), and redirecting the search for a diagnosis in others (beta-OHB < 1.0 mmol/l).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…For this reason, in human medicine, blood ketones are now measured using a hand-held electrochemical sensor that measures 3-HB in 30 sec using capillary whole blood samples [1,25,27,28]. This method is actually the recommended method for diagnosis and monitoring of the treatment of DKA, and can be used for the home monitoring of diabetic patients [1,10,12,18,25,26,27,28]. …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, in human medicine, blood ketones are now measured using a hand-held electrochemical sensor that measures 3-HB in 30 sec using capillary whole blood samples [1,25,27,28]. This method is actually the recommended method for diagnosis and monitoring of the treatment of DKA, and can be used for the home monitoring of diabetic patients [1,10,12,18,25,26,27,28]. …”
Section: Introductionmentioning
confidence: 99%
“…Two retrospective emergency-department studies have shown that capillary point-of-care β-OHB is 100% sensitive for DKA (8,9). Charles et al (10) likewise found that β-OHB was 100% sensitive in a prospective study of seven DKA patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of previous literature, we assumed that the true sensitivity of β-OHB for detecting DKA was between 98 and 100% and determined that a sample including 54 cases of DKA would confirm this point estimate with a confidence limit no lower than 90% (812). The study was stopped after the 54th DKA patient was enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…Because concentrations of up to 0.25 mmol/l may commonly be found after an overnight fast, concentrations above 0.3 mmol/l have been regarded as significantly elevated [44][45][46][47]. However, several studies have compared bedside values with laboratory samples [48,35,49], and found a consensus that, using either method, a value of 3.0 mmol/l should be used as the cut-off for diagnosing DKA, or at the very least, the concentration at which urgent medical attention should be sought [35,41,47,50]. Previous work has shown that urine ketone testing and capillary testing had sensitivities of 95-100% in diagnosing DKA (using 3.0 mmol/l as cut-off), but that the capillary testing was significantly faster, and had higher specificity (78-94% vs. <50%) [49][50][51][52][53][54][55].…”
Section: Further Limitations Of Urine and Blood Testingmentioning
confidence: 99%
“…However, several studies have compared bedside values with laboratory samples [48,35,49], and found a consensus that, using either method, a value of 3.0 mmol/l should be used as the cut-off for diagnosing DKA, or at the very least, the concentration at which urgent medical attention should be sought [35,41,47,50]. Previous work has shown that urine ketone testing and capillary testing had sensitivities of 95-100% in diagnosing DKA (using 3.0 mmol/l as cut-off), but that the capillary testing was significantly faster, and had higher specificity (78-94% vs. <50%) [49][50][51][52][53][54][55]. Thus, whilst capillary and urine ketone concentrations are both excellent at ruling out DKA, the use of capillary ketones has the advantage of sparing unnecessary time and expensive laboratory investigation because their use is likely to reduce the number of false positive results.…”
Section: Further Limitations Of Urine and Blood Testingmentioning
confidence: 99%